Congklak Game Based Learning for Early Childhood Numeracy Growth: Pembelajaran Berbasis Permainan Congklak untuk Pertumbuhan Kemampuan Numerasi pada Anak Usia Dini - Putri Mayasari; Choirun Nisak Aulina (Academia Open, 2025)
General Background Early childhood education emphasizes concrete and play based activities to stimulate cognitive and numeracy development during the golden age period. Specific Background In one kindergarten classroom, children’s counting skills were low because learning relied mainly on worksheets and less engaging media. Knowledge Gap Limited use of traditional game based learning created a need for contextual strategies that actively involve children in numeracy practice. Aims This study aimed to improve early childhood numeracy skills through the implementation of the traditional congklak game. Results Using classroom action research with 11 children, data from observation and tests showed progressive improvement from 9% achievement in the pre cycle to 27% in cycle I and 81% in cycle II after structured congklak activities and gradual modification of game materials. Novelty The study applied staged seed quantities and reward supported play to scaffold counting performance systematically. Implications The findings indicate that traditional game based instruction provides an engaging classroom strategy to support number recognition, counting, and simple operations in early childhood settings. Keywords: Congklak Game, Early Childhood Education, Numeracy Skills, Classroom Action Research, Game Based Learning Key Findings Highlights: Achievement rose from very low baseline to high mastery after two cycles Gradual manipulation of seeds simplified number operations for children Play centered sessions promoted active participation and sustained attention